Influences of Vitamin A on Vaccine Immunogenicity and Efficacy - Penkert, Rhiannon R.; Rowe, Hannah M.; Surman, Sherri L.; Sealy, Robert E.; Rosch, Jason; Hurwitz, Julia L. (Frontiers in Immunology, 2019)
Vitamin A deficiencies and insufficiencies are widespread public health concerns in developing countries, and may be gaining prevalence in industrialized nations. To combat vitamin A deficiency (VAD), the World Health Organization recommends high-dose vitamin A supplementation (VAS) in children 6-59 months of age in locations where VAD is endemic. This practice has significantly reduced all-cause death and diarrhea-related mortalities in children, and may have in some cases improved immune responses toward pediatric vaccines. However, VAS studies have yielded conflicting results, perhaps due to influences of baseline vitamin A levels on VAS efficacy, and due to cross-regulation between vitamin A and related nuclear hormones. Here we provide a brief review of previous pre-clinical and clinical data, showing how VAD and VAS affect immune responses, vaccines, and infectious diseases. We additionally present new results from a VAD mouse model. We found that when VAS was administered to VAD mice at the time of vaccination with a pneumococcal vaccine (Prevnar-13), significantly increased pneumococcus (T4)-specific antibodies were significantly improved. Preliminary data further showed that after challenge with Streptococcus pneumoniae, all mice that had received VAS at the time of vaccination survived. This was a significant improvement compared to vaccination without VAS. Data encourage renewed attention to vitamin A levels, both in developed and developing countries, to assist interpretation of data from vaccine research and to improve the success of vaccine programs.